2014
DOI: 10.1021/ic502006s
|View full text |Cite
|
Sign up to set email alerts
|

Field-Induced Slow Magnetic Relaxation in Cobalt(II) Compounds with Pentagonal Bipyramid Geometry

Abstract: Field-induced slow magnetic relaxation was observed for air-stable mononuclear cobalt(II) compounds with pentagonal bipyramid geometry. These are the first examples of such behavior observed in the seven-coordinated mononuclear 3d metal compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 42 publications
14
92
1
Order By: Relevance
“…82 In other cases the data have been fit only with a Raman term when the energy barrier did not match the energy difference between states. 26,34,8386 In another system, the dependence of τ was fit with Orbach, Raman and direct terms although in one of these cases the Raman term was found to be zero. 87 while in the other the direct was zero.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…82 In other cases the data have been fit only with a Raman term when the energy barrier did not match the energy difference between states. 26,34,8386 In another system, the dependence of τ was fit with Orbach, Raman and direct terms although in one of these cases the Raman term was found to be zero. 87 while in the other the direct was zero.…”
Section: Resultsmentioning
confidence: 99%
“…2,919 In contrast, Co( ii ) SMMs with other coordination environments, e.g. , tri-, 20 penta-, 2123 hexa-, 2433 hepta- 34,35 and octa-coordinated, 36 are less common.…”
Section: Introductionmentioning
confidence: 99%
“…The fitted n-value is lower than n = 4.9 or 8.7 found in other sevencoordinate Co(II) complexes with easy plane anisotropy. 35 To conclude, the analyses of AC susceptibility data and relaxation times showed that both Orbach and Raman processes could be present in 3.…”
Section: Inorganic Chemistrymentioning
confidence: 87%
“…The (117). Adapted with permission from [212], [227], and [226]. Copyright 2013 American Chemical Society.…”
Section: Hepta-coordinated Complexesmentioning
confidence: 99%